Chemotherapy combined with lenvatinib and PD-1 may be a potential better alternative option for advanced unresectable intrahepatic cholangiocarcinoma: a retrospective real-world study - Dong, Zhitao; Sui, Chengjun; Lu, Jiongjiong; Guo, Junwu; Duan, Kecai; Wang, Kui; Geng, Li; Dai, Binghua; Yang, Jiamei (Frontiers in Immunology, 2024)
Background: Currently, the prognosis of advanced intrahepatic cholangiocarcinoma (ICC) is poor, and the current treatment methods are not effective. Objective: The aim of this study was to evaluate the anticancer efficacy of chemotherapy combined with PD-1 inhibitors and tyrosine kinase inhibitors (TKIs) in patients with ICC. Methods: We retrospectively screened patients with advanced intrahepatic cholangiocarcinoma (ICC) who received chemotherapy combined with lenvatinib and PD-1. We evaluated overall survival (OS), progression-free survival (PFS), the objective response rate (ORR), the disease control rate (DCR), the tumor shrinkage rate, and safety. Results: We enrolled 95 patients with ICC and divided them into three groups with a median follow-up duration of 15.1 months. The chemotherapy group (chemo-regimen group), chemotherapy combined with immune checkpoint inhibitors (dual-regimen group), and chemotherapy combined with lenvatinib (triple-regimen group) had median OS times of 13.1 months, 20.8 months, and 39.6 months, respectively. Notably, the triple-regimen group had a significantly longer OS than did the chemo-regimen and dual-regimen groups. The chemo-regimen group, dual-regimen group, and triple-regimen group reported median PFS durations of 4.8 months, 11.9 months, and 23.4 months, respectively. Both combination groups exhibited significantly longer PFS than the chemotherapy-only group (P<0.05). The ORRs of the chemo-regimen, dual-regimen, and triple-regimen groups were 18.2%, 55.5%, and 54.7%, respectively. The DCRs were 72.7%, 90%, and 96.2%, respectively, indicating significantly better outcomes in the combination therapy groups. Conclusion: The combination of chemotherapy with PD-1 inhibitors and lenvatinib demonstrates considerable efficacy and tolerability as a treatment strategy for patients with advanced ICC.